IMPLEMENTATION OF KURIKULUM 2013 (K13) USING SEMESTER CREDIT SYSTEM IN BIOLOGY AT SMART EKSELENSIA INDONESIA - Mokhammad Reza Azhary; Bibin Rubini; Rifki Risma Munandar (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Indonesian education is always developed. One of the innovations is the availability of educational programs to accommodate students to complete study, according to their abilities. The purpose of this research is to describe implementation of Kurikulum 2013 (K13) with Semester Credit System in biology learning. There are four research focuses; planning, organizing, implementing and evaluating. This research is qualitative research with analytical descriptive method. The research was carried out from February to June, 2021, with teachers as informants. The data collected online to avoid spread of COVID-19. The results of research obtained are the planning of biology at SMART Ekselensia Indonesia with additional credits, organizing biology learning using elaboration theory and integrating of Technology Pedagogical Content Knowledge (TPACK), implementation refers to learning designs and learning models according to curriculum demands, and collaboration-based models and using a scientific approach, and learning evaluation includes three assessment domains; cognitive, affective and psychomotor.